1934
DOI: 10.1021/ja01323a045
|View full text |Cite
|
Sign up to set email alerts
|

A New Synthesis of Aldehydo Sugar Acetates1

Abstract: When heated at or above its melting point, 8-ethylcaffeine sublimes, forming fine interwoven needles. Like 8-methylcaffeine, it is quite stable toward acids but is easily decomposed in alkalies. Solubility in 100 cc. of water is 0.6 g. at 25°and 2.0 g. at 100°. It is moderately soluble in cold alcohol and quite soluble in boiling alcohol. The crystals came down from either a water or alcohol solution as bundles of very small colorless needles.Attempts to prepare 8-ro-propylcaffeine and 8-re-butylcaffeine by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1971
1971
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…The method, which employs sodium nitrite and aqueous hydrochloric acid, is the most classic and extensively used. 138 Already in the 1930s carbohydrates like pentaacetates of glucose 139 and mannose 140 were regenerated from their oximes by sodium nitrite and hydrochloric acid in a small portion at a time (Scheme 17). In the 1940s, in a study about the deoximation of ketoximes of bile acids with nitrosating agents, it was suggested that the reaction proceeds through a probable pernitroso intermediate, 141 which readily decomposed to give nitrous oxide and the corresponding ketones (Scheme 18).…”
Section: Nitrosating Agentsmentioning
confidence: 99%
“…The method, which employs sodium nitrite and aqueous hydrochloric acid, is the most classic and extensively used. 138 Already in the 1930s carbohydrates like pentaacetates of glucose 139 and mannose 140 were regenerated from their oximes by sodium nitrite and hydrochloric acid in a small portion at a time (Scheme 17). In the 1940s, in a study about the deoximation of ketoximes of bile acids with nitrosating agents, it was suggested that the reaction proceeds through a probable pernitroso intermediate, 141 which readily decomposed to give nitrous oxide and the corresponding ketones (Scheme 18).…”
Section: Nitrosating Agentsmentioning
confidence: 99%
“…Other methods of converting oximes to ketones using reagents such as cerium salts (62), sodium nitrite (63), and zinc metal (64) were found to be less successful. Hydrolysis by the sodium bisulfite method (46) gave a 45% yield when reacted with a mixture of E-17 and 2-17 oximes (1 :I).…”
Section: N-methylcyclopent-2-enylrnethylamine (41)mentioning
confidence: 99%
“…2 Initially, in the oxidative deoximation, stoichiometric amounts of inorganic and organic oxidants were used to promote the deoximation of ketoximes, which were always accompanied by plenty of unwanted waste (Scheme 1a). 3 Recently, catalytic oxidative deoximation using H 2 O 2 or oxygen as the terminal oxidant has been developed to meet the requirements of modern synthetic chemistry. 4,5 It is worth mentioning that Jang provided a useful photooxidative deoximation of ketoximes (Scheme 1b), and Yu's group contributed catalytic protocols to realize the formation of aromatic ketones and aldehydes from corresponding oximes by taking advantage of the unique property of selenium reagents (Scheme 1c).…”
mentioning
confidence: 99%